Effect of Modification Methods of Wheat Straw Fibers on Water Absorbency and Mechanical Properties of Wheat Straw Fiber Cement-Based Composites - Demin Jiang; Penghui An; Suiping Cui; Shiguo Sun; Jingzong Zhang; Tianfu Tuo (Advances in Materials Science and Engineering)
Five modification methods are adopted for wheat straw fibers (WSFs). The effects of modification methods on the water absorbency of wheat straw fiber/wheat straw fiber cement-based composite (WSFCC) and the mechanical properties of WSFCC are analyzed. The crystallinity, chemical structure, and micromorphology of WSFs and WSFCC 28-day specimens are characterized by XRD, FTIR, and SEM methods. The results show that the water absorption of WSFs modified with sodium silicate solution, pure acrylic acid emulsion, and silicone waterproof emulsion surface spraying is 10.67%, 5.18%, and 1.05% lower than that of unmodified WSFs, respectively. Alkali modification is the ideal method for improving the strength of WSFCC. Establishing a fitting formula of the relationship between water absorption of WSFs and strength of WSFCC specimens has important theoretical and practical guiding significance for development and application of WSFCC.